Electron scattering effects at physisorbed hydrogen molecules on break-junction electrodes and nanowires formation in hydrogen environment - Maas, M. van der; Vasnyov, S.; Hendriksen, B.L.M.; Shklyarevskii, O.I.; Speller, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The physisorption of hydrogen molecules on the surface of gold and other coinage metals was studied usingdistance tunneling spectroscopy. We observed strong N-shaped deviation of the tunnel current (resistance) vs distance dependences from the exponential one. Such deviations are difficult to explain in the framework of the Tersoff–Hamann approximation. We suggest the scattering of the tunneling electrons by H2 molecules as origin for observed effect. We found that this phenomenon is also common for strongly adsorbed organic molecules with one anchoring group. Pulling Au, Cu and Pt nanowires at 22 K in hydrogen environment show that the electrodes of break junctions are still connected up to very low conductances of 10–4–10–6 G0 through hydrogen–metal one-atom chains.